Simple and high‐performance cell balancing control strategy. Issue 9 (29th June 2022) - Chen, Zilong; Liao, Wenjun; Li, Pingfei; Tan, Jinhui; Chen, Yuping
Abstract: The basis for judging whether the battery pack is balanced is generally whether the voltage of the battery cell is consistent because the voltage of the battery cell is very easy to obtain. However, when the voltage of battery cells is the same and the battery management system (BMS) turns off the equalization, it will get poor balance performance. In this paper, a new balancing strategy is proposed, while the calculated state of charge (SOC) difference between the battery cells instead of the voltage reaches the set value, the BMS turns on or off, and the difference in the SOC between battery cells is obtained by adding a small amount of calculation to the difference in voltage between battery cells, due to the long balancing time of the battery, the battery will enter a steady state at the end of balancing, based on the voltage difference of battery cell, the voltage drop generated by the balancing current on the ohmic resistance and polarization resistance is added, combined with the open circuit voltage (OCV)‐SOC curve, the difference in battery voltage can be indirectly converted into a difference in SOC. This strategy will appropriately delay the battery balancing time to make up for the drop in the voltage of the balanced battery cell after the BMS turns off the balancing. In this paper, the proposed strategy and performance are analyzed in detail, the experimental platform is designed to verify, and the battery pack is tested under static and discharge conditions. Although the equalization goal is the same voltage between battery cells, using the voltage‐based equalization strategy, the voltage difference between the battery cells is 8 and 6 mV, respectively, while the strategy proposed in this paper is 2 and 3 mV, which has better performance. Abstract : In this study, we propose a new control strategy to help lithium‐ion batteries operate safely and reliably, which is very simple and easy to implement and can be applied to many battery applications such as energy storage.